Four way effective traffic management system - Mehraj, Fahad Sharif; Humayun, Samin Bin; Hossain, Md. Shafayet; Addree, Asfi Adrin (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.